2015
DOI: 10.5539/gjhs.v7n4p375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupressure on Fatigue in Women With Multiple Sclerosis

Abstract: Introduction:Multiple sclerosis (MS) is the most common cause of progressive neurological disability. The prevalence of MS is much more common in women than men. The women are exposed to a variety of symptoms including fatigue. Acupressure is a noninvasive procedure that can be used to control symptoms including fatigue. The aim of the study was to evaluate the effect of acupressure on fatigue in women with multiple sclerosis.Methods:A randomized clinical trial was conducted on 100 women with MS at Tehran MS A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…An unblinded RCT58 found that acupressure, which stimulates acupoints but does not use needles, significantly reduced fatigue compared with placebo. The authors found that acupressure reduced fatigue score (Fatigue Severity Scale) by 26% at a 4-week follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…An unblinded RCT58 found that acupressure, which stimulates acupoints but does not use needles, significantly reduced fatigue compared with placebo. The authors found that acupressure reduced fatigue score (Fatigue Severity Scale) by 26% at a 4-week follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, pain is one of the most important priorities that could be relieved with both pharmacological and nonpharmacological methods,[ 8 ] hence, using of nonpharmacologic interventions will be an alternative due to the abundant side effects of the available drugs such as opioids. [ 9 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the sample in their study only included patients with ALL; therefore, other types of acute and chronic leukemia could be areas of research for future studies. Moreover, this study only considered one of the problems of leukemia patients, and the effect of acupressure should be studied on the other problems of these patients, such as pain, fatigue, and sleep disorders (20).…”
Section: Acupressurementioning
confidence: 99%
“…A study was conducted by Bastani et al (20) (2011) in Iran in order to determine the effects of acupressure on the nausea and vomiting caused by chemotherapy in children with acute lymphoblastic leukemia (ALL). Therefore, since this method is safer than acupuncture, more studies should be conducted on the beneficial effects and safety of this method in leukemia patients.…”
Section: Acupressurementioning
confidence: 99%